2012
DOI: 10.1007/s00253-012-4032-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactobacillus salivarius CECT 5713, a strain isolated from human milk: from genotype to phenotype

Abstract: Lactobacillus salivarius CECT 5713, isolated from human milk, has immunomodulatory, anti-inflammatory and antiinfectious properties, as revealed by several in vitro and in vivo assays, which suggests a strong potential as a probiotic strain. In this work, the relationships between several genetic features of L. salivarius CECT 5713 and the corresponding phenotypes were evaluated. Although it contains a plasmid-encoded bacteriocin cluster, no bacteriocin biosynthesis was observed, possibly due to a 4-bp deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 44 publications
2
40
0
1
Order By: Relevance
“…Antibacterial properties against pathogenic bacteria have been reported for L. salivarius CECT5713 due to the production of antimicrobial compounds such as lactate, acetate, and hydrogen peroxide [14]. This strain also harbors a bacteriocin cluster located in a megaplasmid that contains several genes that would allow the biosynthesis of several bacteriocins, but a deletion at the beginning of the regulatory system results in the absence of any bacteriocin production [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibacterial properties against pathogenic bacteria have been reported for L. salivarius CECT5713 due to the production of antimicrobial compounds such as lactate, acetate, and hydrogen peroxide [14]. This strain also harbors a bacteriocin cluster located in a megaplasmid that contains several genes that would allow the biosynthesis of several bacteriocins, but a deletion at the beginning of the regulatory system results in the absence of any bacteriocin production [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, L. salivarius CECT5713 that was isolated from human milk and infant feces of a healthy mother-child pair has been shown to have remarkable probiotic potential because it had high rate of survival in simulated gastrointestinal tract conditions and strong adherence to mucus and intestinal cells in vitro , stimulated the expression of mucin-encoding genes, and produced antimicrobial compounds [1417]. More recently, its complete genome has been sequenced [18], and its genetic features, such as proteins potentially involved in human molecular mimetism, may explain its immunomodulatory, anti-inflammatory, and anti-infectious properties [19, 20]. Moreover, its safety and health beneficial effects have been proved in animal models and in human clinical assays [2023].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies suggest that selected bacteria of the maternal gastrointestinal microbiota can access the mammary gland through an entero-mammary pathway. The mechanism involves dendritic cells and CD18 + cells, which can take up nonpathogenic bacteria from the gut lumen and carry them to the lactating mammary gland [38, 39]. Boix-Amoros et al confirmed the presence of live bacteria moving inside the extracellular matrix of immune cells [30].…”
Section: Introductionmentioning
confidence: 99%
“…С учетом того, что антигенстимулиро-ванные дендритные клетки кишечника перемещаются, распространяясь в отдаленные слизистые оболочки (дыха-тельные пути, мочеполовой тракт), слюнные и слезные железы, а также в молочные железы кормящих женщин [42], напрашивается предположение о том, что дендрит-ные клетки могут содержать живые кишечные бактерии и попадать в ткань лактирующей молочной железы. Это предположение получило научное обоснование в рабо-тах нескольких независимых исследовательских групп [43][44][45][46]. Таким образом, к настоящему времени можно считать доказанным, что кишечные бактерии достигают молочной железы путем переноса мононуклеарами, при-чем процесс этот регулируется гормонами, активируясь в последнем триместре беременности и снижаясь после окончания периода лактации.…”
unclassified